Experimental investigation of selective catalytic reduction system on CI engine for NOx reduction using urea and animal urine as catalyst - Tirpude, Raju B.; Katare, Pravin; Rajurkar, Sanjay; Awari, Gajanan; Karagoz, Yasin; Dalkilic, Ahmet Selim; Wongwises, Somchai (INDERSCIENCE ENTERPRISES LTD, 2023)
Selective catalyst reduction systems are the popular and efficient post-combustion nitrogen oxides reduction techniques utilised in the automotive and power generating industries. They involve a chemical reaction in which vaporised ammonia is gathered from the mixture of urea and purified water. Conversion of nitrogen oxide to nitrogen and water is the main target. In this NOx reduction system, costlier reductants have been utilised, which increases the operating cost of the vehicle. The methodologies adopted in this research work are the use of natural resources as a catalyst. Production of a modified selective catalyst reduction device was conducted in the first process. Secondly, the collection and preparation of diesel exhaust solution using various pure urea and urine (cow and sheep urines) with varying concentrations was carried out to inject the tailpipe via the selective catalyst reduction system's feed pump to assist in reducing the oxide of nitrogen. In a conclusion, there can be an important improvement in the oxide of nitrogen emissions using urea, cow, and sheep urines in the modified selective catalyst reduction. The urine-based solution shows a 2.3% reduction in NOx emission as compared to the urea-based solution.
Keywords: CI engine; SCR; NOx; catalyst; cow urine; sheep urine; DIESEL; PERFORMANCE; EMISSIONS; COMBUSTION; FUEL; Environmental Sciences & Ecology